Pembinaan Anak Pelaku Tawuran sebagai Implementasi Keadilan Rehabilitatif di Sentra Handayani Jakarta - Wahyu Nugroho; Afiah Nurrizky; Muliadi Nur (ILIN Institute, 2024)
This research aims to analyze the correctional efforts done by Sentra Handayani Jakarta towards child perpetrators of brawls. In this context, Sentra Handayani Jakarta is present as a social rehabilitation institution that prioritizes the provision of education in fostering child brawlers. This research uses a legal empirical research method with a field research approach. Data collection techniques in the form of interviews were used to examine the process of mentoring and rehabilitation of child perpetrators of brawls at Sentra Handayani Jakarta. The results showed that the rehabilitation efforts of child perpetrators of brawls at Sentra Handayani Jakarta were colored by quite complex problems. This is related to the tough diversion efforts with victims, to the parents of children who are not cooperative. However, not a few child perpetrators of brawls have also been successfully rehabilitated so that they can be accepted back into society.